Automated culture: introduction. Issue 1 (2nd January 2023) - Andrejevic, Mark; Fordyce, Robbie; Li, Luzhou; Trott, Verity
ABSTRACT: Automation has a long history in cultural production, but the contemporary moment presents a range of new possibilities and demands for the deployment of automated and autonomous systems in the shaping of our cultural and social worlds. The cultural implications of the deployment of automated systems for producing, curating, and distributing a growing range of cultural texts and artifacts extend beyond the realm of content to encompass their pace, rhythm, and scale. Understanding the significance of these shifts remains a central task for cultural studies research that builds on the field's historical engagement with the entwinement of cultural practices, social relations, and power. This theme issue builds on the historical and recent concerns of cultural studies to provide a range of approaches to the cultural significance of automation. Given the scope of the transformations, the coverage of possible topics is indicative rather than exhaustive. The articles in this collection range across the realms of automated news curation, credit scoring, image curation, deep fakes, data science, the gig economy, and content moderation. They engage with possible responses to the real and potential pathologies of automation in the cultural realm – while highlighting the links between culture, politics, and economics. Taken together they develop a range of critical approaches to the sometimes creeping, sometimes galloping automation of cultural production, curation, and distribution. While stressing the moments of historical continuity with earlier forms of bureaucratic and administrative rationality, they simultaneously indicate that we are, in many ways, still in the very early stages of a process that is likely to encompass an expanding range of cultural practices and texts.